STUDI EKSPERIMENTAL PERBANDINGAN ALIRAN MELINTASI DUA SILINDER SIRKULAR DAN SILINDER ELIPS TERSUSUN TANDEM DAN INTERAKSINYA TERHADAP DINDING DATAR - Helmizar Helmizar (ROTOR, 2012)
The study was conducted to obtain information about the characteristics of fluid flow that touches the surface of the bluff body.  Bluff body in the form of circular and elliptical cylinders  and brought near a wall. Phenomenon found is used to predict the aerodynamic loads on the bluff body and leads to a drag reduction efforts.Elliptic cylinder and circular cylinder are arranged in tandem position with longitudinal distance (L/D = 1.5) and gap distance variation (G/D) between cylinders and  flat wall are 0.067, 0.133, 0.2, 0.267. Fluid flow characteristics investigated experimentally on open loop wind tunnel. The experimental results are used to explain flow interaction phenomenoum which is resulted coefficient pressure distribution (Cp) on the cylinder, on the flat wall and velocity distribution on the upstream and downstream. The placement of the elliptic cylinder at G/D = 0.267 exhibits the lowest drag. The whole research was done on the Reynolds number 53574 based on circular cylinder diameter. Keywords: circular cylinder, elliptic cylinder, drag force.